Implementation of Hygiene and Sanitation in the Bar Section at Oyster Dealer Beach Haus, Batu Belig, Kerobokan Kelod, North Kuta, Badung, Bali - I Made Thio Setiawan; I Gusti Nyoman Wiantara; Ni Luh Putu Sri Widhiastuty (Brilliant International Journal Of Management And Tourism, 2026)
This study examines the implementation of hygiene and sanitation in the bar section of Oyster Dealer Beach Haus Batu Belig, Kerobokan Kelod, North Kuta, Badung, Bali. The research was motivated by the strategic role of food and beverage services in supporting tourism quality and by the contamination risks faced by bar operations in a semi-open coastal environment. A descriptive qualitative approach supported by limited quantitative data was applied. Data were collected through direct observation, semi-structured interviews with the Bar Manager and Bartender, and documentation related to operational procedures, equipment cleanliness, ingredient handling, and work area sanitation. The findings indicate that hygiene and sanitation have been implemented fairly well through standard operating procedures, personal hygiene practices, beverage hygiene, environmental cleaning, and bar equipment sanitation. However, several obstacles remain, including inconsistent employee compliance, time pressure during peak hours, high equipment usage, difficult-to-clean areas, and drainage problems. Management addresses these issues through supervision, regular training, daily briefings, clearer task distribution, general cleaning, drainage checks, and additional equipment. The study contributes practical recommendations for strengthening hygiene consistency and service quality in coastal bar operations.